Computer based instrumentation system for pressure measurement in matlab application - Nurliyana, Mohd Johari (2008)
This project presents a mechanism of collecting data from a process control plant. Generally, this project based on process control that used the instrument to measure pressure in kPa and converted the output to the current in mA. This project used the equipments from the experiment and built the system using MATLAB, graphical user interface (GUI) to manipulate the data. From the data, students can do investigations and analysis such as plot the graph of the output and error, and uncertainty of the measurement for the calibration of the pressure transmitter. This mechanism will help students during their laboratory session. In order to support the system, data acquisition card, PCI 1710HG will be used to transfer data from pressure transmitter to the computer. The result will be displayed in the GUI including the data that have been transfer from the instrument to the computer. The graph of five-point calibration and error also shown. In addition, the results of the calculation for average and error of the data, standard deviation, combined standard uncertainty and the effective degree of freedom to get the uncertainty are included in the study analysis. Students can use this proposed mechanism to do the data analysis which is very convenience for the lab session. This system will benefit not only the students but also for the instructor.